Difference between revisions of "009B Sample Midterm 2, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Replaced content with "<span class="exam"> Evaluate the integral: ::<math>\int e^{-2x}\sin (2x)~dx</math> <hr> '''<u>Solution</u>''' 009B Samp...")
 
(3 intermediate revisions by the same user not shown)
Line 3: Line 3:
 
::<math>\int e^{-2x}\sin (2x)~dx</math>
 
::<math>\int e^{-2x}\sin (2x)~dx</math>
  
 +
<hr>
 +
[[009B Sample Midterm 2, Problem 4 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;
 
|-
 
|Integration by parts tells us <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math>
 
|-
 
|How would you integrate <math style="vertical-align: -15px">\int e^x\sin x~dx?</math>
 
|-
 
|
 
::You could use integration by parts.
 
|-
 
|
 
::Let <math style="vertical-align: -5px">u=\sin(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=\cos(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
 
|-
 
|
 
::Thus, <math style="vertical-align: -15px">\int e^x\sin x~dx\,=\,e^x\sin(x)-\int e^x\cos(x)~dx.</math>
 
|-
 
|
 
::Now, we need to use integration by parts a second time.
 
|-
 
|
 
::Let <math style="vertical-align: -5px">u=\cos(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=-\sin(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math> So,
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
\displaystyle{\int e^x\sin x~dx} & = & \displaystyle{e^x\sin(x)-(e^x\cos(x)-\int -e^x\sin(x)~dx}\\
 
&&\\
 
& = & \displaystyle{e^x(\sin(x)-\cos(x))-\int e^x\sin(x)~dx.}\\
 
\end{array}</math>
 
|-
 
|
 
::Notice, we are back where we started. So, adding the last term on the right hand side to the opposite side,
 
|-
 
|
 
::we get <math style="vertical-align: -13px">2\int e^x\sin (x)~dx\,=\,e^x(\sin(x)-\cos(x)).</math>
 
|-
 
|
 
::Hence, <math style="vertical-align: -15px">\int e^x\sin (x)~dx\,=\,\frac{e^x}{2}(\sin(x)-\cos(x))+C.</math>
 
|}
 
  
'''Solution:'''
+
[[009B Sample Midterm 2, Problem 4 Detailed Solution|'''<u>Detailed Solution</u>''']]
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|We proceed using integration by parts. Let <math style="vertical-align: -5px">u=\sin(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math>. Then, <math style="vertical-align: -5px">du=2\cos(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}</math>.
 
|-
 
|So, we get
 
|-
 
| &nbsp;&nbsp; <math style="vertical-align: -14px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}-\int \frac{e^{-2x}2\cos(2x)~dx}{-2}=\frac{\sin(2x)e^{-2x}}{-2}+\int e^{-2x}\cos(2x)~dx</math>.
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we need to use integration by parts again. Let <math style="vertical-align: -5px">u=\cos(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math>. Then, <math style="vertical-align: -5px">du=-2\sin(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}</math>.
 
|-
 
|So, we get
 
|-
 
| &nbsp;&nbsp; <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}-\int e^{-2x}\sin(2x)~dx</math>.
 
|-
 
|
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Notice that the integral on the right of the last equation in Step 2 is the same integral that we had at the beginning of the problem.
 
|-
 
|So, if we add the integral on the right to the other side of the equation, we get
 
|-
 
| &nbsp;&nbsp; <math>2\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}</math>&thinsp;.
 
|-
 
|Now, we divide both sides by 2 to get
 
|-
 
| &nbsp;&nbsp; <math>\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-4}+\frac{\cos(2x)e^{-2x}}{-4}</math>&thinsp;.
 
|-
 
|Thus, the final answer is <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
| &nbsp;&nbsp; <math>\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>
 
|}
 
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:10, 12 November 2017

Evaluate the integral:


Solution


Detailed Solution


Return to Sample Exam